Pharmacokinetics of recombinant human annexin A5 (SY-005) in patients with severe COVID-19 - Tschirhart, Brent J.; Lu, Xiangru; Mokale Kognou, Aristide Laurel; Martin, Claudio M.; Slessarev, Marat; Fraser, Douglas D.; Leligdowicz, Aleksandra; Urquhart, Bradley; Feng, Qingping (Frontiers in Pharmacology, 2024)
Objective: Annexin A5 is a phosphatidylserine binding protein with anti-inflammatory, anticoagulant and anti-apoptotic properties. Preclinical studies have shown that annexin A5 inhibits proinflammatory responses and improves organ function and survival in rodent models of sepsis. This clinical trial aimed to evaluate the pharmacokinetic (PK) properties of the recombinant human annexin A5 (SY-005) in severe COVID-19. Methods: This was a pilot randomized, double-blind, placebocontrolled trial. Severe COVID-19 patients were randomly assigned to receive intravenous 50 µg/kg (low dose, n=3), 100 µg/kg (high dose, n=5) of SY-005 or placebo (n=5) every 12 hours for 7 days. Plasma SY-005 levels were assessed using enzyme-linked immunosorbent assay (ELISA) and the PK parameters were determined using non-compartmental analysis. Results: All patients treated with SY-005 had a normal baseline estimated glomerular filtration rate (eGFR, 104-125 mL/min/1.73 m 2 ). Both low and high doses of SY-005 were cleared within 6 hours after intravenous administration. Plasma maximum concentrations (Cmax), half-life, clearance and volume distribution of low and high doses of SY-005 were 402.4 and 848.9 ng/mL, 0.92 and 0.96 hours, 7.52 and 15.19 L/h, and 9.98 and 20.79 L, respectively. Daily pre-dose circulating annexin A5 levels were not significantly different when SY-005 was administered at the low or the high dose 12-hour intervals. There was no significant effect on activated partial thromboplastin time (aPTT) or INR (international normalized ratio of prothrombin time) during 7 days of SY-005 treatment. Conclusion SY-005 doses of 50 and 100 µg/kg were detectable and subsequently cleared from the plasma in severe COVID-19 patients with normal baseline renal function. There was no significant plasma SY-005 accumulation 6 hours after drug administration and coagulation was not altered during 7 days of treatment. Clinical trials Registration: This study was registered with ClinicalTrials.gov (NCT04748757, first posted on February 10, 2021).